A career and learning transitions model for those experiencing labour market disadvantage - Cameron, Roslyn (Sage Publications, 2009)
Research investigating the learning and career transitions of those disadvantaged in the labour market has resulted in the development of a four-component model to enable disadvantaged groups to navigate learning and career transitions. The four components of the model include: the self-concept; learning and recognition; career and life planning; and new literacies. The focus of this paper will be on the career and life planning component. The research utilised a sequential mixed model design, which consisted of two phases. Phase one of the research involved a Learning Survey of approximately 250 labour market program participants in which quantitative data analysis techniques were used. Phase two involved the development of the model and testing in the fi eld. A formative evaluation of the modelin the field was undertaken, utilising a combination of both qualitative and quantitative data collection and analysis. The fi eld test was undertaken with a labour market program for women over 45 years of age wishing to re-enter the workforce. The research has resulted in the development of a model that offers career development researchers and practitioners an alternative holistic, group-based and community-based approach to career development for disadvantaged groups.